Long-term complications of definitive chemoradiotherapy for esophageal cancer using the classical method. (23rd January 2017) - Ito, Hitoshi; Itasaka, Satoshi; Sakanaka, Katsuyuki; Araki, Norio; Mizowaki, Takashi; Hiraoka, Masahiro
Abstract: Chemoradiation therapy is widely used to treat both inoperable and operable patients, and is less invasive than surgery. Although the number of long-term survivors who have received chemoradiation therapy is increasing, the long-term toxicity pattern and cumulative incidence of toxicity regarding this modality are poorly understood. Classically, chemoradiation therapy for esophageal cancer consists of an anterior–posterior field and a subsequent oblique boost field. We retrospectively analyzed patients who were treated with definitive chemoradiation therapy for esophageal cancer using this classical method from 1999 to 2008. For the assessment of toxicity, the National Cancer Institute Common Toxicity Criteria Version 3.0 was adopted. A total of 101 patients were analyzed. The median follow-up time was 16 months for all patients and 62 months for the surviving patients. Eleven patients experienced late toxicities of ≥Grade 3. Two patients died of late toxicities. The 3- and 5-year cumulative incidences for the first late cardiopulmonary toxicities of ≥Grade 3 were 17.4% and 20.8%, respectively. Cardiopulmonary effusions were observed within the first 3 years of completion of the initial treatment in seven out of eight patients. Sudden death and cardiac ischemia were observed over a 10-year period. Older age was found to be a risk factor for late toxicity after definitive chemoradiation therapy for esophageal cancer. Substantial toxicities were observed in patients who had received chemoradiation therapy for esophageal cancer using the classical method. To minimize the incidence of late toxicity, more sophisticated radiation techniques may be useful.